'A horizon of national economic opportunity' – industrialization and crisis in 1970s Wilhelmshaven. (4th May 2020) - Eiben, Jörn
Abstract: Scholars from various disciplines argue that the 1970s formed a historical watershed. Several arguments rely on the notion of a significant change in the modes of production, labour and consumption – a change usually coined as de-industrialization, which had severe economic, social and cultural repercussions on numerous cities. These repercussions are frequently phrased in semantics of crisis. The article will present an exemplary case that sits uneasily with this master narrative. Wilhelmshaven, a medium-sized city in north-west Germany, witnessed significant changes in the 1970s, too – but not away from, but towards industrialization, and throughout the industrializing phase, diagnoses of crisis played a major role in stabilizing the process. Analysing Wilhelmshaven's industrialization, which took place between the late 1960s and the mid-1980s, will shed light on two aspects: first, the effects industrialization had on the city's socio-economic structure; secondly, the effects different crises and their diagnosis had on the process. In doing so, the article will link perspectives from urban history with theoretical concepts of crisis and, thus, attempt to provoke a closer look at cities of the 1970s.